2017
DOI: 10.1007/s00402-017-2847-z
|View full text |Cite
|
Sign up to set email alerts
|

The distance of the gluteal nerve in relation to anatomical landmarks: an anatomic study

Abstract: IntroductionGluteal insufficiency is of concern with lateral approaches to total hip arthroplasty. Damage to the branches of the superior gluteal nerve may cause degeneration of the innervated muscles. The direct anterior approach exploits the intermuscular and internerval interval between tensor fasciae latae laterally and sartorius and rectus femoris muscle medially. In this study, the distance of the superior gluteal nerve in relation to anatomical landmarks was determined.Materials and methodsTwo experienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 42 publications
(45 reference statements)
1
18
0
1
Order By: Relevance
“…We agree with Putzer et al. [ 13 ] that the use of a flexible ruler could lead to some measurement deviation. However, we made each measurement through consensus with all 3 authors before documentation.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…We agree with Putzer et al. [ 13 ] that the use of a flexible ruler could lead to some measurement deviation. However, we made each measurement through consensus with all 3 authors before documentation.…”
Section: Discussionsupporting
confidence: 92%
“…[ 30 ] investigated various nerve palsies in relation to total hip arthroplasty and found just 36% of those with complete neurologic injuries recovered fully. With effects as severe as recurrent dislocations, the functional deviations generated from these injuries can significantly reduce the patient’s quality of life [ 13 , 16 ]. And even if the nerve is only partially and/or transiently injured, the hip is destabilized by its lack of full abductor moment (and at increased risk of dislocation) while it recovers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Postoperative atrophy and degeneration of the TFL with a consecutive loss of function can be caused by direct mechanical damage to the muscle or injury to the SGN's terminal branches [16]. Sacred cadaver studies reported that placement of retractors and cauterization of the lateral circumflex femoral artery could, directly and indirectly, lead to injury of the terminal branches of the SGN during DAA THA [13,14]. This can lead to severe functional restrictions that severely affect the patient's everyday life because the TFL is an important thigh abductor, which holds the pelvis horizontal during the stance phase of the gait and balances the body weight and the non-weight-bearing leg when walking [1,8,22].…”
mentioning
confidence: 99%